The Effectiveness of the Universities Entrepreneurship Ecosystem in Shaping the Students’ Entrepreneurial Career Choices: Evidence from UAE Context - Rania Gamal El Din Sheir (2025)
This study investigates the factors that influence the establishment and functioning of the university entrepreneurship ecosystem (UEE) and its impact on the student entrepreneurial career choice. This research utilises the case-study methodology to conduct an evidence-based analysis of the current theoretical framework. It aims to validate the role of its elements through empirical experience, which is gathered from semi-structured interviews with 7 respondents from three private universities in Dubai. The results shows that the business incubators programs have a greater favourable influence on student entrepreneurship compared to official courses and various tiers of networks can facilitate the flow and interchange of resources. In addition, the findings reveal that culture has a crucial role in shaping and fostering individual entrepreneurial behaviour and their clustering in the UEE. Furthermore, the UEE's creation and progress are significantly influenced by strong entrepreneurial vision and enduring commitments, particularly in terms of leadership.